A face (nem tão) oculta das necessidades pedagógicas : uma análise criminológica sobre os sentidos da medida socioeducativa de internação na contemporaneidade - Alves, Mariana de Paula (2014)
This work proposes to undertake a criminological analysis of the meanings attributed to socioeducation in Brazilian courts nowadays. To restrict the object of research, the study is focused on the socio-educative confinement measure in cases involving the commitment of an offense analogous to the crime of theft, through the analysis of the main pleas and arguments present in judgments of the Superior Court of Justice. Highlighting the fact that adolescence is not just a life phase in which there is an acceleration of physical and mental maturation, we based on comprehensive theoretical references in order to facilitate the involvement of a multitude elements that involve transit through physiological changes, cognitive and intellectual, personality and identity, socio-cultural, political-economic, moral, axiological, among others. Given the need for a broader criminological also matrix that behaved different looks on the interfaces between adolescence, transgression and control, found himself in cultural criminology some propositions that we could verify that the bases of these phenomena may reside elements in common. It is to offer a distinctive criminological approach, since it goes beyond the purely structural analysis, to capture widespread tensions arising from processes of economic and cultural globalization. Moreover, amid other theoretical frameworks, it was necessary to resort to some concepts formulated by Pierre Bourdieu, from which it was possible to understand the dynamics of functioning of the legal field and its mechanisms of social reproduction. At the end, we tried to understand how it is possible to make use of the equation Judiciary "pedagogical needs reiteration infraction" to apply the socio measure of internment in response to illegal acts committed without the use of violence or serious threat to person.